Multiple tachykinins and their receptors characterized in the gastropod mollusk Pacific abalone: Expression, signaling cascades, and potential role in regulating lipid metabolism - Lee, Seungheon; Kim, Mi Ae; Park, Jong-Moon; Park, Keunwan; Sohn, Young Chang (Frontiers in Endocrinology, 2022)
Tachykinin (TK) families, including the first neuropeptide substance P, have been intensively explored in bilaterians. Knowledge of signaling of TK receptors (TKRs) has enabled the comprehension of diverse physiological. However, TK signaling systems are largely unknown in Lophotrochozoa. This study identified two TK precursors and two TKR isoforms in the Pacific abalone Haliotis discus hannai (Hdh), a marine gastropod mollusk, and characterized Hdh-TK signaling. Hdh-TK peptides derived from Hdh-TK1 and -TK2 precursors harbored protostomian TK-specific FXGXRamide or unique YXGXRamide motifs at the C-termini. There are two isoforms of Hdh-TKRs, Hdh-TKRL with a longer C-terminal intracellular domain (ICD) and Hdh-TKRS with a shorter ICD. A phylogenetic analysis showed that lophotrochozoan TKRs, including Hdh-TKRs, form a monophyletic group distinct from arthropod TKRs and natalisin receptor groups. Although reporter assays demonstrated that all examined Hdh-TK peptides activate intracellular cAMP accumulation and Ca2+ mobilization in Hdh-TKR-expressing mammalian cells, Hdh-TK peptides with N-terminal aromatic residues and C-terminal FXGXRamide motifs were more active than shorter or less aromatic Hdh-TK peptides with a C-terminal YXGXRamide. In addition, we showed that ligand-stimulated Hdh-TKRs mediate ERK1/2 phosphorylation in HEK293 cells and that ERK1/2 phosphorylation is inhibited by PKA and PKC inhibitors. In three-dimensional in silico Hdh-TKRL binding modeling, higher docking scores of Hdh-TK peptides were consistent with the lower EC50 values in the reporter assays. The transcripts for Hdh-TK precursors and Hdh-TKR were highly expressed in the neural ganglia, with lower expression levels in peripheral tissues. When abalone were starved for 3 weeks, Hdh-TK1 transcript levels, but not Hdh-TK2, were increased in the cerebral ganglia (CG), intestine, and hepatopancreas, contrasting with the decreased lipid content and transcript levels of sterol regulatory element-binding protein (SREBP). At 24 h post-injection in vivo, the lower dose of Hdh-TK1 mixture increased SREBP transcript levels in the CG and hepatopancreas and accumulative food consumption of abalone. Higher doses of Hdh-TK1 and Hdh-TK2 mixtures decreased the SREBP levels in the CG. Collectively, our results demonstrate the first TK signaling system in gastropod mollusks and suggest a possible role for TK peptides in regulating lipid metabolism in the neural and peripheral tissues of abalone.